Corporate Governance and Accounting Conservatism of Quoted Non-Financial Firms in Nigeria - Egbadju, Lawrence (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study investigates the impact of some corporate governance attributes on accounting conservatism in Nigeria. The study covers the period from 2005 to 2020 of 75 non-financial firms listed on the floor of the Nigerian Exchange Group (NXG). The results of the generalized method of moments (GMM) reveal that while four of the variables board size (BODS), managerial ownership (MOWN), audit committee size (ACS) and number of foreign directors (NFODIR) are positively significant with accounting conservatism; two of the variables chief executive officer with military experience (CEOME) and board independence (BODI) are negatively significant with it but board gender diversity (BGDIV) is insignificant. Again, while the Big4 as well as the number of foreign directors (NFODIR) are positively significant; foreign income (FINCOME) as well as the industry (IDUM) and yearly (YDUM) dummy variables are positively insignificant. The study makes some recommendations such as management should maintain or increase the present level of board size, managerial ownership, audit committee size and the number of foreigners in the board since these variables allowed management to stick to prudence in financial reporting for the period under review.